“Managing Staff WFH in Crisis Times” - How Are Teacher Education Managers Supporting Staff Working Remotely at an Odel College? - Fulufhelo Mukhathi; Samson L Tshabalala; Christy J Kotze; Micheal M Van Wyk (JETL (Journal of Education, Teaching and Learning), 2022)
The sudden onslaught of the Covid-19 pandemic changed how university managers operate. Staff working from home (WFH) needed support and teacher education managers (TEM) played an important role in giving such support. This study is underpinned by the crisis leadership theory and ubuntu-oriented management style. The aim of this exploratory study is to ascertain the support strategies provided by TEM to staff WFH during the Covid-19 pandemic. To achieve the aim, this study investigates motivational support TEM provided to staff WFH during the pandemic. The aim included establishing which stress management techniques TEM used to support staff WFH and explore communicative tools used to support staff WFH.  The constructivist-interpretivist lens is foregrounding the qualitative single case research, exploring the kind of support that six distance managers provided to staff WFH at an open distance e-learning university. Results revealed that staff WFH were acknowledged and rewarded for hard work and excellence. Several web-based video-conferencing sessions were offered through online Teams webinars, seminars, workshops and stress management techniques. Further research needs to be undertaken to determine, through a mixed-method design, how TEM employed stress management techniques for staff WFH, which may yield different results.